The Effect of Job Evaluation, Work Environment and Supervision on Work Effectiveness of Public Works and Spatial Planning Office Employees in Lahat Regency - Dori Arizona; Yuhanis Ladewi; Harun Samsuddin (Journal of Indonesian Management, 2023)
This study aims to analyze the effect of job evaluation, work environment and supervision on the work effectiveness of employees of the Public Works and Spatial Planning Office of Lahat Regency. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Data analysis techniques using validity test, reliability test, classical assumption test using, normality test, heteroscedasticity test and multicollinearity. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial tests and coefficient of determination. The results of the study obtained that job evaluation has a significant effect on the work effectiveness of employees of the Public Works and Spatial Planning Office of Lahat Regency. The work environment has a significant effect on the effectiveness of the work of the Public Works and Spatial Planning Office of Lahat Regency. Supervision has a significant effect on the work effectiveness of employees of the Public Works and Spatial Planning Office of Lahat Regency Keywords: Job evaluation, work environment, supervision and work effectiveness.